Religious Metaphors in Public Speeches of Turkish Politicians - Polova, Olena (Journal of History Culture and Art Research, 2020)
Religion is an integral part of culture of the Turkish people. An important feature of the cultural and socio-political sphere of Turkey is the frequent use of expressions with religious content, among which metaphor is prominent. This study investigates religious metaphors used by Turkish politicians. The data analysis is carried out on the basis of the material obtained by means of a self-compiled corpus, which consists of public speeches of Turkish politicians (e.g., the President, deputies, and leaders of the main political parties of Turkey) for the period of 2010-2019. The paper claims that the core religious beliefs of the Turks have a great impact on the way they see and perceive the surrounding reality, which is reflected in metaphorical expressions they use. Therefore, Turkish politicians often associate other political figures, political processes, and events of social and political life with religious characters, episodes, and phenomena. This principle formed the basis of the model of “Social and Political Reality is Religion” for its analysis on the metaphoric expressions. The analysis suggests that metaphor is a significant tool of representing Islamic ethics in Turkish public discourse. Despite the fact that a religious metaphoric model is often characterized by positive emotionality, the aforementioned model has both positive and negative connotations.